Bourdieu & Chartier: Sociologist and Historian - Huebner, Daniel R. (Serendipities. Journal for the Sociology and History of the Social Sciences, 2016)
Book Review of: Pierre Bourdieu and Roger Chartier: The Sociologist and the Historian, translated by David Fernbach Cambridge, UK: Polity Press, 2015 Pp. xxii+82 ISBN: 978-0745679587 Price: $49,95